'I could help, but . . .': A dynamic sensemaking model of workplace bullying bystanders. (December 2020) - Ng, Kara; Niven, Karen; Hoel, Helge
How do we explain the behaviour of employees who encounter workplace bullying but fail to intervene, or sometimes even join the perpetrator? We often assume that bystanders witnessing bullying will restore justice, but empirical research suggests that they may also behave in ways that continue, or worsen, its progression. Recent theories have attempted to explain the process of bystander behaviour in response to general mistreatment, but the range of acknowledged behaviours is limited, and their scope is restricted to isolated incidents rather than complex, dynamic phenomena like workplace bullying. We offer a new model of bystander behaviours in workplace bullying. We use sensemaking theory to explain how appraisals of severity, victim deservingness and efficacy influence bystanders to enact a range of possible behaviours, and how post-hoc sensemaking utilizing moral disengagement affects how bystanders appraise and respond to future bullying. We explain the influence of the social context on sensemaking and the reciprocal influence that individual bystanders have on the social context. Our model explains how bystander behaviours change over time in response to repeated incidents and how bystanders' responses affect other bystanders' appraisals and the bullying process, therefore providing a dynamic perspective on the role of bystanders in workplace bullying.